YUSUF KHAS HOJIB'S WORK "QUTADG‘U BILIG" AND THE IMAGE OF THE FATHER IN IT (Scientific journal of the Fergana State University, 2026)
This article presents an in-depth analysis of Yusuf Khos Hajib’s “Qutadgu Bilig” as a representative work of the Karakhanid period literature. The artistic and aesthetic value of the work, along with its thematic dimensions, is explored through hermeneutic, structural-poetic, psychological, and contextual methods of analysis. The main focus of the study is on the image of the father, whose broad interpretation reveals the author’s unique descriptive style, mastery in character creation, and the contemporary relevance of the functions assigned to these images. The article examines the social-political context and issues of the period, the human “self” and inner world, moral values, and the problem of properly organizing life as the primary themes. Through the father figure, the idea of shaping the “perfect human” — morally, spiritually, and socially mature personality — is advanced. This research plays an important role in illuminating the spiritual and aesthetic values of medieval Turkic literature and aids modern readers and scholars in gaining a deeper understanding of the work.